Knowledge Management And Malaysian Small-Medium Enterprises (SMEs) Export Performance: Mediating Role Of Innovation - Khaw, Jia Qi (2020)
Small and Medium Enterprises (SMEs) play an important role in contributing and supporting the economy of the nation. Since there is a strong bond between SMEs and nation’s economy, it is critical in paying attention towards the development of SMEs. However, SMEs in Malaysia are not developed in the full strength. The commerce world is changing rapidly and organizations that are not developed well will struggle to survive the competitive market. In such, the resources and values that carries by knowledge could lead organization to gain a competitive advantage in the market. Knowledge works as the capital and asset in driving the organization’s success. Organizations are encouraged to develop their capabilities in the process of knowledge management in which moving them into more competitive and innovative in the market. Innovation came to mind for organization to reinvest and reshape themselves in order to standstill in the competitive market.